THE MANAGEMENT OF PINE STANDS SITUATED OUTSIDE THEIR HABITAT - Cristinel CONSTANDACHE; Lucian DINCĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Harvested wheat is a complex ecosystem with a rich enzymatic activity, located in the germ, contaminated with microorganisms and potentially infested with insects. Wheat quality assurance during storage represents a set of technical measures which are applied to direct the physical-chemical and biological processes within the mass of grains, to the purpose of maintaining them under good conditions, with minimum quality and quantity losses. This work presents a study on the influence of common wheat (Triticum aestivum, ssp. vulgare) belonging to the Romanian variety Dropia, intended for the obtaining food-grade flour. The prophylactic treatments were conducted using groups from the T+ toxicity group (K-obiol EC 25), in view of preserving the wheat under optimal conditions. The obtained results prove the efficiency of the post-harvest prophylactic treatments, which contribute to the preservation of wheat quality during extended storage. The applied treatment ensured protection from pests and, according to the determinations, it did not significantly change the initial values of the quality indicators for the stored wheat.